Immunogenetics 2019
DOI: 10.5772/intechopen.75951
|View full text |Cite
|
Sign up to set email alerts
|

Immunoassay Techniques Highlighting Biomarkers in Immunogenetic Diseases

Abstract: Diagnosis of autoimmune diseases is crucial for the clinician and the patient alike. The immunoassay techniques most commonly used for this purpose are immunohistochemistry, ELISA, and Western blotting. For the detection of more specific biomarkers or the discovery of new ones for diagnostic purposes and as therapeutic targets, microarray techniques are increasingly used, for example, protein microarray, Luminex, and in recent years, surface plasmon resonance imaging. All of these technologies have undergone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…ELISA usually uses coated wells with recombinant proteins or linear peptides produced in transfected bacteria (e.g. E. coli) or baculovirus-infected insect cells (Engvall and Perlmann, 1972;Possee, 1997;Manole et al, 2018).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…ELISA usually uses coated wells with recombinant proteins or linear peptides produced in transfected bacteria (e.g. E. coli) or baculovirus-infected insect cells (Engvall and Perlmann, 1972;Possee, 1997;Manole et al, 2018).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…Various studies have suggested biomarkers for liver cancer, and the effort to identify additional markers is ongoing ( 40 ). Numerous methods, including immunohistochemistry, ELISA and western blotting, have previously been used in such studies ( 41 , 42 ). However, these methods are relatively time-consuming and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Singleplex immunoassays (i.e. an assay with only one target) are the primary clinical format used at present 70 . While many diseases can rely on single analyte analysis for optimal patient outcomes (e.g.…”
Section: 24 Immunoassay Limitationsmentioning
confidence: 99%